A pilot study of locally available teas as a medicament anti-bacterial effects - Gabriel, Marybeth
The use of medicaments (such as f ormocresol and CMCP) in the endodontic procedure has been practiced successfully by dentists over the years. Recently, studies show that Japanese green tea extracts contain antibacterial properties against organisms inhabiting infected root canals and thus may be useful as a medicament. Here in the Philippines, the locally available Ceylon and Lipton teas, together with the tea shrub, "chaang gubat", were made to undergo sterility tests to eliminate any contamination. These were then tested against 3 common bacterial strains that infect the root canals using the tube dilution method. Statistical analysis reveal that both Lipton and Ceylon teas have antibacterial effects.